(untitled) (Texas Journal of Philology, Culture and History, 2024)
Similar and different aspects of Uzbek and English proverbs. Their origin forms the basis of the article. With clear examples made easy to understand and theories proven. The etymology of proverbs, as a part of folklore, is a fascinating subject that delves into the origins and evolution of these traditional sayings within the fabric of society. Proverbs serve as concise, memorable expressions of wisdom and life truths, often reflecting the values, beliefs, and experiences of a particular culture or community. By examining the etymology of proverbs, scholars and enthusiasts can gain a deeper understanding of the intricate connections between language, culture, and society, while also appreciating the enduring relevance of these timeless expressions of human wisdom